A critical appraisal of continence in bladder exstrophy: Long-term outcomes of the complete primary repair. Issue 4 (August 2016) - Ellison, J.S.; Shnorhavorian, M.; Willihnganz-Lawson, K.; Grady, R.; Merguerian, P.A.
Summary: Introduction: Long-term continence outcomes for patients with bladder exstrophy are lacking in the literature. The complete primary repair of exstrophy (CPRE) is a widely adopted approach that seeks to normalize anatomy at the initial repair, thereby allowing early bladder filling and cycling. Previous reports of continence following CPRE, however, are limited by variable follow-up duration and continence definitions. Objective: To assess continence and factors associated with a positive outcome in a cohort of patients following CPRE with long-term follow-up. Study Design: A retrospective chart review was conducted of all patients with primary bladder closure using CPRE at the present institution for classic bladder exstrophy from 1990 to 2010. Patients <6 years of age or with an incomplete continence assessment at last follow-up were excluded. Continence was defined as voiding volitionally with dry intervals of ≥3 h, which was consistent with other high-volume series in the literature. Results: Twenty-nine of the 52 patients (56%) were eligible for inclusion. Twelve patients were continent at last follow-up, including seven boys and five girls. Mean follow-up for the entire cohort was 148 months. The Summary table displays comparisons between continent and incontinent patients. Of patients achieving continence, 42% did not require further continence operations, while 17% required only one additional continence operation. Discussion: Long-term CPRE continence rates were lower than previously reported, but comparable to other series in the literature. Of those achieving continence, 59% will do so with zero or one additional operation. Sex and osteotomy status were not associated with continence outcomes, although age at follow-up was a predictor of continence, favoring older patients in the present series. The study was limited by lack of standardized, patient-reported continence outcomes and by the retrospective nature of the review. However, the data add to the literature of long-term continence outcomes and are important for counseling families both at initial repair and follow-up. Conclusions: Complete primary repair of exstrophy can achieve continence without additional operations in a subset of patients. Some patients, however, may not achieve continence until adolescence, underscoring the need for long-term urologic follow-up in patients with bladder exstrophy. Table Comparison of continent (C) and incontinent (IC) patients.   Total C ( N  = 12) IC ( N  = 17) P -value Age at OR (days) Mean (SD) 1.8 (1.8) 2.4 (1.8) 0.4527 Osteotomy (%) Yes 3 (25) 7 (41) 0.4475 No 8 (67) 9 (53)   Unspecified 1 (8) 1 (6)   Complications (%) Yes 2 (17) 5 (29) 1 No 10 (83) 12 (71)   Age at last follow-up Mean (SD) 167 (49.3) 134 (42.3) 0.0536 Urodynamic findings Compliance (ml/cm H2 O) 16.0 (5.4) 8.5 (3.8) 0.0041 % Predicted capacity (SD) 75.8 (45.4) 38.0 (15.4) 0.0047 Age at last follow-up (months) Mean (SD) 167 (49.3) 134 (42.3) 0.0536 Statistically significant P -values denoted inbold. OR, operation.